Candidate biomarkers for response to tamoxifen in breast cancer metastatic patients - Cava, Claudia; Bertoli, Gloria; Zoppis, Italo; Mauri, Giancarlo; Gilardi, Maria Carla; Castiglioni, Isabella (13th IEEE International Conference on BioInformatics and BioEngineering, 2013)
Tamoxifen is currently used for the treatment of breast cancer. Response to tamoxifen in metastatic conditions is a primary issue in cancer development. We used a cohort of breast cancer patients, treated or not with tamoxifen, and combined these data with the gene signature of metastatic samples in order to investigate the genetic mechanism of metastasis development, in search of a possible therapeutic effect of tamoxifen in metastatic conditions,. The analysis revealed a group of 21 genes common both to the set of up regulated genes in metastatic BC patients and to the set of down regulated genes in tamoxifen treated patients. These genes could be used as biomarkers for tamoxifen-sensitivity in order to optimize BC treatment.